Reply to Comments on 'Design of Halfband Filters for Orthogonal Wavelets via Sum of Squares Decomposition' - Yu, Runyi; Baradarani, Aryaz (IEEE-Inst Electrical Electronics Engineers Inc, 2009)
[Abstract Not Available]